Information Security Awareness of School Administrators - Karabatak, SongUl; Karabatak, Murat (Ieee, 2019)
The aim of this study is to determine the information security awareness levels of school administrators. The sample of the quantitative study conducted in the scanning model was composed of 174 school administrators selected by the disproportionate element sampling method among the school administrators working in the high schools in the city of Elazig. The Information Security Awareness Scale was used as the data collection tool. The mean, percentage, and frequency techniques, correlation analysis and t-test were used to data analysis. According to the results, school administrators mostly connect to the internet at school and use the internet mostly to do research. Information security awareness level of school administrators is generally above the medium level and the highest level of awareness is the dimension of social media usage. It has been revealed that there is a moderate, negative, and significant relationship between the school administrators' age and their information security awareness level. The awareness level of male school administrators is higher than females in terms of information security. At the end of the study, various suggestions were made about increasing the awareness of school administrators about information security.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: school administrator; information security; information security awareness